Exploring Two Different ranslation Versions of Culinary Specific Terms the Subtitle of lm 'Chef' - Iis Damayanti; M. R. Nababan; Diah Kristina (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2021)
Abstract. This paper attempts to unfold the phenomena of two different translation versions of culinary terms in film ‘Chef’, namely the subtitle version of ‘Siberian’ and of ‘Agent Nas’. The objectives of the study are to describe the translation techniques used in translating the culinary specific terms in each subtitle version and to explain the influence of the translation techniques used towards the accuracy, acceptability, and the readability of the culinary specific term translation. The study is a product, context, and participant-oriented translation research based on qualitative paradigm that employs a case study model. The data collection techniques are document analysis and focus group discussion and the data technique analysis adopt the principles of ethnography manifested in the use of domain, taxonomy, and componential analysis as well as finding cultural values. The result of the study shows that the two subtitlers have different frequency level in using the techniques and that the techniques used affect the quality of the culinary term translation. The most obvious distinction is that Siberian resorts to many pure borrowings compared to Agent Nas. This translates to a good score of accuracy, but potentially reduce the level of acceptability of the translation. In addition, Agent Nas resorts to annotation technique that is meant to improve the understanding of the viewers while Siberian does not. All in all, the overall translation quality of culinary terms produced by the two subtitlers is almost equal with Agent Nas version slightly better than Siberian.Keywords: culinary specific term translation; translation techniques; translation quality; subtitleAbstrak. Penelitian ini berusaha untuk mengungkap fenomena dua versi terjemahan istilah khusus kuliner yang berbeda dalam film ‘Chef’, yakni versi subtitle ‘Siberian’ dan versi ‘Agent Nas’. Tujuan penelitian ini adalah untuk mengungkap teknik penerjemahan yang digunakan dalam menerjemahkan istilah khusus kuliner pada masing-masing versi subtitle dan menjelaskan dampak penggunaan teknik penerjemahan tersebut terhadap tingkat keakuratan, keberterimaan, dan keterbacaan terjemahan istilah khusus kuliner. Penelitian ini merupakan penelitian penerjemahan yang berorientasi pada produk, konteks, dan partisipan yang berdasarkan pada paradigma kualitatif yang berbentuk studi kasus. Teknik pengumpulan data yang digunakan adalah analisis dokumen dan diskusi kelompok fokus dan teknik analisis data yang digunakan menerapkan prinsip etnografi dalam bentuk analisis dokumen, taksonomi, komponensial, serta menemukan tema budaya. Hasil penelitian menunjukkan bawha dua penerjemah tersebut memiliki tingkat frekuensi penggunaan teknik penerjemahan yang berbeda dan teknik yang digunakan berdampak pada kualitas terjemahan yang dihasilkan. Perbedaan yang paling mencolok adalah penggunaan teknik peminjaman murni oleh Siberian jauh lebih sering dilakukan dibandingkan dengan Agen Nas. Namun demikian, Agent Nas juga ditemukan menggunakan teknik anotasi yang dimaksudkan untuk memudahkan penonton untuk memahami terjemahan sedangkan Siberian sama sekali tidak menggunakannya. Secara garis besar, kualitas keseluruhan terjemahan istilah khusus kuliner yang dihasilkan oleh kedua versi subtitle hampir sama dengan nilai Agent Nas sedikit lebih tinggi dari Siberian. Kata kunci: terjemahan istilah khusus kuliner; teknik penerjemahan; kualitas terjemahan; subtitle